Cop and the Sociologist : Investigating Diversity in German Police Forces. - Thériault, Barbara (Bielefeld : Transcript Verlag, 2013)
Drawing on the sociology of Max Weber, Barbara Thériault investigates today's relations toward difference within German police forces. Accompanying and interviewing police officers whose job it is to contribute to the acknowledgement of difference, the sociologist outlines three ideal types of actors - an empathetic, a principled, and an opportunist one - and the motives underlying their actions. A fourth type, the specialist, is conspicuously absent. Why is that so? Solving this enigma helps depicting the relations to difference within police forces: it points to a specific "spirit" of diversity and a singular way to apprehend the individual in Germany.
Frontmatter -- Contents -- List of Illustrations -- Preface -- I. Max Weber, the Sociologist, and the Police Officer -- II. Dealing With Difference. Four Portraits and a Half -- III. A Three-Dimensional Picture -- Appendix -- BIBLIOGRAPHY -- Index.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Police -- Social aspects -- Germany; Cultural pluralism -- Germany; Diversité culturelle -- Allemagne; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; SOCIAL SCIENCE / Popular Culture; Cultural pluralism; Germany